Demographics and ultrasonography findings of mastalgia in a tier 2 city of India - Shivangi Tomar; Rekha Agrawal; Harshit Shrivastava; Akhilendra Singh Parihar (Asian Journal of Medical Sciences, 2024)
Background: Breast pain is the second most common breast symptom (after breast lump) for which women seeks medical attention. Breast pain can affect daily life, including sleeping, or physical, social, and work-school life. Mastalgia is one of the common causes for women in tier 2 city visiting health care facility but there are only few studies which focus on demographic findings and ultrasonographic findings in mastalgia. Aims and Objectives: The objective of this study was to study demographics of breast pain in a tier 2 city and ultrasound evaluation of mastalgia. Materials and Methods: In this prospective study, 143 patients presenting with mastalgia irrespective of focality, duration, or cyclical nature were included. In these patients, we studied demographic profile and ultrasonographic findings in mastalgia. Results: About 37% women were in 20–29 years of age group and least number was in 70–79 years of age group. About 86% of women in our study were in reproductive age group. Most patient with mastalgia have associated palpable lump (58%) followed by 43% patients with mastalgia and nipple discharge, only 27% of patients have mastalgia alone whereas 4% women have pain with skin changes. The majority (49%) of mastalgia cases fall under the breast imaging-reporting data system (BI-RADS)-I category while cases in BI-RADS-IV and V category were 2 and 1, respectively. Conclusion: Women in their reproductive age group and in their 3rd decade of life are more prone for mastalgia. Ultrasonography is also helpful in detecting cancers in setups where routine mammography is not possible.